Structure-aided optimization of 3-O-β-chacotriosyl ursolic acid as novel H5N1 entry inhibitors with high selective index. Issue 18 (15th September 2019) - Liao, Yixian; Chen, Lizhu; Li, Sumei; Cui, Zi-ning; Lei, Zhiwei; Li, Hui; Liu, Shuwen; Song, Gaopeng
Graphical abstract: 3- O -β-chacotriosyl ursolic acid amide derivative 14 displayed strong anti-H5N1 (IC50 = 1.05 μM) and the selectivity index greater than 952. Abstract: Currently, entry inhibitors contribute immensely in developing a new generation of anti-influenza virus drugs. Our earlier studies have identified that 3- O -β-chacotriosyl ursolic acid (1 ) could inhibit H5N1 pseudovirus by targeting hemagglutinin (HA). In the present study, a series of C-28 modified pentacyclic triterpene saponins via conjugation with a series of amide derivatives were synthesized and their antiviral activities against influenza A/Duck/Guangdong/99 virus (H5N1) in MDCK cells were evaluated. The SARs analysis of these compounds revealed that introduction of certain amide structures at the 17-COOH of ursolic acid could significantly enhance both their antiviral activity and selective index. This study indicated that the attachment of the methoxy group or Cl atom to the phenyl ring at the ortho - or para -position was crucial to improve inhibitory activity. Mechanism studies demonstrated that these title triterpenoids could bind tightly to the viral envelope HA to block the attachment of viruses to host cells, which was consistent with docking studies.